العقيدة ودورها في التمكين: العوامل والتحديات: `Aqidah and its Role in Empowerment: Factors and Challenges - KURT, Nurullah; Syed Abdul Rahman, Syed Mohammad Hilmi; Ahmad Fadzillah, Nurrulhidayah (Online Journal of Research in Islamic Studies, 2020)
This research is an attempt to detect that the concept of "role of faith in empowerment of the vulnerable people in the earth and its factors as well as challenges in the light of the Holy Quran" is undoubtedly a historical fact that witnessed by Muslims for a long period. The researcher believes that the weakness of the today’s Muslims is in lack of use of the existing empowerment factors they have stalled for various reasons. Therefore, it is the intention of the researcher to undertake an insight to explain and analyze the most important factors of the issue through three themes: i) Confidence in victory of Allah and Jihad in His path, ii) Fear of Allah and His threats, and iii) Dependence on Allah. The researchers also critically and analytically answered three questions posed in this article with logic and literature abstracted evidences: Where is dignity of the believer from the Qur’anic verse that says “And to Allah belongs [all honor], and to His Messenger, and to the believers, but the hypocrites do not know.” (al-Munafiqun, 63:8). Why is there abandonment today in the world of Islam? While Allah says, “and incumbent upon Us was support of the believers.” (al-Rum, 30:47). Why is it necessary to be confident in victory and jihad in order to achieve it? The author concluded the research with an objective comparison between Muslims and non-Muslim, that the problem lies in Muslims themselves and he rejected the flimsy, illogical and non-scientific reasoning.